Evolution of conventional and non-conventional energy - Milla L., Luis (2002)
Conventional and non-conventional energy is a necessity in the modern which humans can not do without the world, however there are several problems, such as; scarcity, cost, depletion, uptake, contamination, for that reason should be track the evolution of each of these types of energy which not only prioritize their installation cost or the price of KHH, but opportunity to have the energy for a particular purpose.